The Effect of Bullying at Yarmouk University on Students' Performance from their Point of View - Sedqy Al-Rashdan, Hanady (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to identify the effect of bullying at Yarmouk University on students’ performance from their point of view. The study sample consisted of (500) university students selected randomly. To achieve the study objectives, a questionnaire was used. The study showed that the level of bullying and students’ performance at Yarmouk University were moderate. It also showed a statistically significant difference in the effect of bullying on students’ performance at Yarmouk University due to academic year, in favor of second year students, while there was no statistically significant difference in the effect of bullying on students’ performance at Yarmouk University due to gender and type of faculty. The study revealed that there is statistically significant effect of bullying on students' performance at Yarmouk University. In light of the results some recommendations were provided.